PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINKâ€“PAIRâ€“SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VA SDN 005 SIAK HULU - Masni, Masni; Witri, Gustimal; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is motivated by the fact that is found in the class VA SDN 005 Siak Hulu, which shows the results of learning in IPA is still relatively low. Formulation the problem is this research is : â€œDocs the application of cooperative type Think Pair Share (TPS) to model can improve learning outcome in IPA students class VA SDN 005 Siak Hulu?â€. This research aims to improve learning outcomes in IPA students class VA SDN 005 Siak Hulu with application of cooperative type Think Pair Share (TPS). The hypothesis og this study is that if applied learning model cooperative type Think Pair Share (TPS) it can improve learning outcomes in IPA student class VA SDN 005 Siak Hulu. This study was conducted in SDN 005 Siak Hulu in April 2016. This from is research is classroom action research (PTK) are planned as much as two cycle. The subjects were students of class VA SDN 005 Siak Hulu academic year 2015/2016 which amounted to 22 people consisting of 11 men and 11 women. Based on the results of research of teacher activity sheet seen rising each meeting. At the first meeting of the first cycle of 70%, the second meeting of the first cycle 75%, at the fourth meeting of the second cycle of 85%, and the fifth meeting of the second cycle of 95%. Student activity observation sheet also increased at every meeting. At the first meeting of the first cycle of 60%, the second meeting of the first cycle of 70%, at the fourth meeting of the second cycle of 80%, and the fifth meeting of the second cycle of 95%. Mastery learning outcomes to repeat at first cycle increased 24,73% from the base score of 61,59 to 76,82. In the second cycle increased by 33,58% to 97,50. The average value in the base score 61,59, UH then the first cycle to 76,82 with an increase of 15,23. Where as the second cycle of the average value of UH become 35,91 with an increase of 97,50. So that research result are consistent with the hypothesis.Key Word : Learning Model Cooperative Type Think Pair Share (TPS)